Pembelajaran Materi Bangun Datar Pada Siswa SD Kelas IV Dengan Menggunakan Pendekatan Konstruktivisme - Puspita, Yanti; Ristiana, Muhammad Ghiyats (COLLASE (Creative of Learning Students Elementary Education), 2020)
The research aims to analyze (1)scenarios and implementation constructivism approach, (2) the response of teachers and students, (3) The difficulties experienced by students in complete a task. The subject of this research are 15 students of fourth (IV) grade of SDN Palintang Jaya. 5 Students high level, 5 Students middle, 5 students low level. This research is a qualitative methods. The scenario and point to finding froms the students can more active teacher lesson learned by means of concrete using media and social interaction between teachers or friends. A good response from teachers and students. The difficulties experienced by students in complete a task, because the students are still unable to use mathematics concept. Based on the result of this research shows that reach mathematical understanding ability, after following construtivism approach.